2020
DOI: 10.1038/s41398-020-0837-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress induces insertion of calcium-permeable AMPA receptors in the OFC–BLA synapse and modulates emotional behaviours in mice

Abstract: Stress increases the risk of neuropsychiatric disorders, such as major depression. Exposure to stress has been reported to induce various neuronal changes, such as alterations in synaptic transmission and structure. However, a causal link between stress-induced neural circuit alterations and changes in emotional behaviours is not well understood. In the present study, we focused on a projection pathway from the orbitofrontal cortex (OFC) to the basolateral nucleus of the amygdala (BLA) as a crucial circuit for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…The significant reduction of GluA2 in the right BLA of juvenile male rats after early stress is similar to the reduced GluA2 expression observed in the adult BLA after chronic stress (Yi et al, 2017) and could contribute to a postsynaptic mechanism for LTP facilitation. Chronic stress has also been shown to enhance the inward rectification of AMPAR in the BLA (Kuniishi et al, 2020), suggesting an increase in AMPARs lacking the GluA2 subunit. Given the regulation of calcium permeability of AMPAR by the GluA2 subunit (for review, see Wright and Vissel, 2012), a reduction of GluA2 could enhance LTP formation via increasing calcium influx (Jia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction of GluA2 in the right BLA of juvenile male rats after early stress is similar to the reduced GluA2 expression observed in the adult BLA after chronic stress (Yi et al, 2017) and could contribute to a postsynaptic mechanism for LTP facilitation. Chronic stress has also been shown to enhance the inward rectification of AMPAR in the BLA (Kuniishi et al, 2020), suggesting an increase in AMPARs lacking the GluA2 subunit. Given the regulation of calcium permeability of AMPAR by the GluA2 subunit (for review, see Wright and Vissel, 2012), a reduction of GluA2 could enhance LTP formation via increasing calcium influx (Jia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our prior research has shown that this procedure results in pharmacologically relevant blood alcohol (BAC; Faccidomo et al, 2009). BAC was not measured in the present study to prevent behavioral disruption and potential stress-induced insertion of calcium-permeable AMPARs (Kuniishi et al, 2020), which are functionally regulated by TARP γ-8 (Bats et al, 2013).…”
Section: Operant Self-administration Trainingmentioning
confidence: 94%
“…CP-AMPARs are involved in the pathogenesis of Alzheimer disease (Whitehead et al, 2017), Parkinson disease (Kobylecki et al, 2010), epilepsy (Friedman and Koudinov, 1999), drug addiction (Conrad et al,Figure 6. Gabapentin and the a2d-1CT-Tat C terminus peptide restore heteromeric GluA1/GluA2 receptors diminished by a2d-1 coexpression Article ll OPEN ACCESS 2008), chronic stress (Kuniishi et al, 2020), neurogenic hypertension (Li et al, 2012), and ischemic stroke (Noh et al, 2005). Given the well-recognized role of CP-AMPARs in these neurological disorders, it is crucial to determine to what extent a2d-1 mediates the increased synaptic CP-AMPARs under these conditions so that rational treatments can be designed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, α2δ-1 is highly expressed in many brain regions and is expected to similarly regulate AMPAR subunit composition. CP-AMPARs are involved in the pathogenesis of Alzheimer disease ( Whitehead et al, 2017 ), Parkinson disease ( Kobylecki et al, 2010 ), epilepsy ( Friedman and Koudinov, 1999 ), drug addiction ( Conrad et al, 2008 ), chronic stress ( Kuniishi et al, 2020 ), neurogenic hypertension ( Li et al, 2012 ), and ischemic stroke ( Noh et al, 2005 ). Given the well-recognized role of CP-AMPARs in these neurological disorders, it is crucial to determine to what extent α2δ-1 mediates the increased synaptic CP-AMPARs under these conditions so that rational treatments can be designed.…”
Section: Discussionmentioning
confidence: 99%